Test study on basic static characteristics of cable supported barrel vault structure - Qiao, Wentao (2015)
By combining single layer cylindrical latticed shell (SLCLS) and beam string structure, a new-style prestressed spatial structure cable supported barrel vault structure (CSBV) is formed. Taking a practical CSBV roject as prototype, a scaled model with a scale of 1:15 is designed and fabricated, the static loading test is carried out. Research results indicate that the characteristics of the prototype structure can be reflected by this model test. As the load increases, the change rule of the test values of the cables' forces agree with that of theoretical values. The two outmost cables' forces are generally smaller than the other interior cables' forces. The cables' forces in the symmetrical places keep closer. For rods' forces and nodal displacements of CSBV, the test values and theoretical values both keep closer. The differences between test values and theoretical values increases with the load. The test values are larger than the theoretical values, but the change rule still matches. Compared with SLCLS in the same condition, the rods' forces and nodal displacements of the CSBV are both smaller, and the mechanic characteristics of CSBV are more efficient.